2006
DOI: 10.1002/ca.20172
|View full text |Cite
|
Sign up to set email alerts
|

Innervation patterns of the inferior glenohumeral ligament: Anatomical and biomechanical relevance

Abstract: Although the Inferior Glenohumeral Ligament (IGHL) has a well known mechanical and proprioceptive relevance in shoulder stability, the interrelation of the ligament's anatomical disposition/innervation has not actually been described previously. The purpose of the study was to determine the IGHL innervation patterns and relate them to dislocation. Forty-five embalmed and 16 fresh-frozen human cadaveric shoulders were studied. Masson's Trichrome staining detailed the intraligamentous nerve fiber arrangements. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The axillary nerve most commonly bifurcates into the anterior and posterior branches within or posterior to the quadrangular space in 55% (Gelber et al 2006), 87% (Uz et al 2007), and 100% (Tubbs et al 2005) of specimens. Uz et al (2007) found the point of bifurcation proximal to the quadrangular space in 13%, whereas Gelber et al (2006) found this arrangement in 38% of specimens.…”
Section: Regional Relationshipsmentioning
confidence: 99%
See 4 more Smart Citations
“…The axillary nerve most commonly bifurcates into the anterior and posterior branches within or posterior to the quadrangular space in 55% (Gelber et al 2006), 87% (Uz et al 2007), and 100% (Tubbs et al 2005) of specimens. Uz et al (2007) found the point of bifurcation proximal to the quadrangular space in 13%, whereas Gelber et al (2006) found this arrangement in 38% of specimens.…”
Section: Regional Relationshipsmentioning
confidence: 99%
“…Uz et al (2007) found the point of bifurcation proximal to the quadrangular space in 13%, whereas Gelber et al (2006) found this arrangement in 38% of specimens.…”
Section: Regional Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations